Nutrient removal in tropical subsurface flow constructed wetlands under batch and continuous flow conditions - Gersberg, Richard M. (2013)
The aim of this investigation was to evaluate the influence of batch versus continuous flow on the removal efficiencies of chemical oxygen demand (COD), nitrogen (N) and total phosphorus (TP) in tropical subsurface flow constructed wetlands (SSF CW). The quantitative role of the higher aquatic plants in nutrient removal in these two operational modes was also investigated. Results indicated no significant difference (p > 0.05) in COD removal between batch and continuous flow modes for either the planted or unplanted treatments. Furthermore, the batch-loaded planted wetlands showed significantly (p < 0.05) higher ammonium removal efficiencies (95.2%) compared with the continuously fed systems (80.4%), most probably because the drain and fill batch mode presented systematically more oxidized environmental conditions. With respect to TP removal, for both planted and unplanted beds, there was significant enhancement (p < 0.05) in batch flow operation (69.6% for planted beds; 39.1% for unplanted beds) as compared to continuous flow operation (46.8% for planted beds; 25.5% for unplanted beds). In addition, at a 4-day hydraulic retention time (HRT), the presence of plants significantly enhanced both ammonia oxidation and TP removal in both batch and continuous modes of operation as compared to that for unplanted beds. An estimation of the quantitative role of aeration from drain and fill operation at a 4-day HRT, as compared to rhizosphere aeration by the higher aquatic plant, indicated that drain and fill operation might account for only less than half of the higher aquatic plant’s quantitative contribution of oxygen (1.55 g O2 per m2 per day for batch flow versus 1.13 g O2 per m2 per day for continuous flow).